Community participation in sustainable management of community forests: Case study Ban Mae Hong Khrai, Mae Pong Sub-District, Doi Saket District, Chiang Mai Province - Pharcharuen, Winit; Suramati, Phramaha Weerasak; Phrakhrusutaworathammakit, Phrakhrusutaworathammakit; Mahawaro, Phrakhruwinaithornwarawut; Chantawaree, Sukanda (Linguistics and Culture Review, 2021)
The objectives of this research were to 1) study the potential and obstacles in community forest management 2) study the level of community participation in community forest management 3) propose a guideline to promote the participation of sustainable management of community forests. This research methodology for this study includes a combination of both quantitative and qualitative methods. Data for the quantitative method was collected from one representative of each household and it was used to analyze statistics such as; percentage, mean and standard deviation. And data for the qualitative method was collected from the community leaders, Community Forests Committee, People's Representative Representatives from government and private sectors consisting of 16 people, using in-depth interviews, discussion, and questionnaires as research tools. The results of the study showed that the potentials of the community forest were abundant and consist of various biodiversity. The community forest is useful, and it benefits the people because It is a source of food and it generates extra income, it's a learning centre and an ecotourism centre. The major problems and obstacles encountered in the management of the community forest are Participation of the community forest has not yet reached its full potential.